Georgia : Recent Economic Developments and Selected Issues. (IMF Staff Country Reports; Country Report, 2000)
This paper provides an overview of recent economic developments in Georgia. The country has made significant, but incomplete, progress toward establishing the rule of law. The rapid accumulation of wage and social transfers arrears is one of the factors of the worsening poverty. The banking sector reforms have started to yield positive results, particularly with regard to banking system consolidation. The energy sector exchange, trade and payments systems, tax summary, and statistical data on the economic indices of Georgia are presented in the paper.